State of cities : governance for a liveable Chittagong. (Dhaka : BRAC Institute of Governance and Development (BIGD), BRAC University, 2014)
On the urbanization planning of Chittagang City, Bangladesh; a study.
Includes statistical tables.
Includes bibliographical references (pages 127-135)
AAL
Complimentary copy
Keywords: Land use, Urban -- Bangladesh -- Chittagong; Urbanization -- Bangladesh -- Chittagong -- Social conditions